Fancy Nancy Besties For Eternity - O'Connor, Jane; Preiss-Glasser, Robin ([Place of publication not identified] : HarperCollins, 2025)
"For Nancy, a long weekend means fun, fun, and more fun with her best friend, Bree. But, alas! Bree will be away visiting her grandmother, leaving Nancy forlorn--that's a fancy way of saying sad and lonely. Then, at the park, Nancy meets Lily, who is older, fearless, and--ooh la la!--from Paris! Nancy can hardly believe such a glamorous girl wants to be friends. They spend the weekend together, and everything seems parfait (French for perfect)--at least until Bree returns. What will Nancy do?! Will she have room in her heart for two true friends?"--.
new kids book 2025 fall.
Keywords: Friendship in children; Play; Best friends; Parks